One-Stage Multilevel Surgery for Treatment of Obstructive Sleep Apnea Syndrome - Gabriela Bosco (MDPI AG, 2021)
We report the results of one-stage multilevel upper airway surgery for patients who could not tolerate continuous positive airway pressure (CPAP). Patients treated with multilevel surgery at a University Hospital in 2015–2019 were identified from a prospectively maintained database. The inclusion criteria were aged 18–70 years, body mass index (BMI) < 35 kg/m2, apnea–hypopnea index (AHI) > 20, and lingual tonsil hypertrophy grade 3 or 4. Drug-induced sleep endoscopy was performed before surgery in all patients. Multilevel surgery was performed in one stage and included expansion sphincter pharyngoplasty (ESP), coblation tongue base reduction (CTBR), and partial epiglottectomy (PE) as required. The outcome measures were postoperative AHI, time percentage oxygen saturation < 90%, and Epworth Sleepiness Scale (ESS) score. A total of 24 patients were included: median age 49.1 years, average BMI 27.26 kg/m2, and 90% men. Ten patients received ESP plus CTBR plus PE, eight received ESP plus CTBR, and six received ESP plus PE. The mean preoperative AHI was 33.01 at baseline and improved to 17.7 ± 13 after surgery (p < 0.05). The ESS score decreased from 11 ± 5.11 to 7.9 ± 4.94 (p < 0.05). The surgical success rate according to Sher’s criteria was 82.3%. The median follow-up was 23.3 months (range 12–36). These findings suggest that multilevel surgery is a safe and successful treatment of OSAHS.